Classification of transport obligations in civil law - Kumarova, U.K.; Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2019)
The purpose of the research is to analyze the classification of transport obligations under civil law and to identify on this basis certain types of transport obligations. For achievement of goal, the task to study the legal nature of each type of civil law contracts on the provision of transport services is set out. The essence and legal nature of transport contracts are disclosed by conducting a legal analysis of modern legislation that regulates legal relations in various sectors of transport. The theoretical basis of this study is the research of civilians, devoted to the concept and types of transport contracts, the legal regulation of transport obligations. The article touches upon such issues as the classification of transport obligations, including the system of contract of carriage, the legal nature of each type of transport agreement is analyzed, and the issues of identifying a specific group of transport obligations arising from other types of contracts for the provision of compensated services activities are get covered (for example, an agreement on the provision of pilot services, an agreement on rescue, an agreement on the performance of aviation works, an agreement on maritime agency services, etc.). Scientific novelty is conducting a study of the legal regulation of certain types of transport obligations, the development of proposals aimed at improving the civil legislation of the Republic of Kazakhstan.